Contribution Of a Large-Scale HIV Prevention Program on Condom Use by Long-Distance Truck Drivers in India: A Decomposition Analysis - Damodar Sahu; Niranjan Saggurti; Ram Manohar Mishra; Deepika Ganju; Laxmikant Chavan; Arvind Pandey (Medsci Publications, 2016)
Background: This paper examines the impact of the HIV prevention programme among long-distance truck drivers in promoting consistent condom use with paid female partners in India. Methods: The study utilizes data from two rounds of the Integrated Biological and Behavioural Assess met along National Highways (IBBS-NH), 2007 and 2009-10. Using the time location cluster sampling approach, major transshipment locations covering the bulk of India's transport volume along four route corridors were surveyed. Long-distance truck drivers were interviewed about their sexual behaviour, condom use practices, and exposure to HIV prevention interventions. Results: Consistent condom use with paid female partners was increased by 11% among long distance truck drivers from round 1 to round 2 (Total increase 11%). Truckers exposed to intensive program exposure were two times more likely to use condom consistently with paid partners (OR 2.1; 95% CI 1.4-3.1; p-value <0.0001). Out of a total increase in consistent condom use with paid partners, truckers who were exposed to the program contributed 58%. Conclusions: This study results highlight the ability of intensive programs to reach truckers who have sex outside marriage with HIV prevention interventions and promote safe sex practices among them.